The benefits of a pet on the social and emotional development of young children in preschool setting - Angliongto, Angelita Ma. Tiongson (2001)
The study of children's behavior when exposed to animals is still an area of research that is quite new. This, which investigated what benefits a pet has on the social and emotional development of preschool children, is exploratory and descriptive in nature. The subjects were taken from two schools, namely U.P. Child Development Center and The learning Tree Child Growth Center. The children were grouped according to the age range of 4.0-4.11 and 5.0-5.11. The class routines per teacher were also investigated in order to gain a clearer understanding of when the desired behavior would most frequently occur. The information on the observed social and emotional behavior of the children in relation to the rabbit was gathered through a naturalistic observation of the children. An event sampling form was used in order to facilitate note taking. The results were validated by several interviews with the teacher after the observations. Because of the exploratory and qualitative nature of this study the frequencies of the accumulated traits, which were categorized into social and emotional skills, were the basic tools used for data analysis. A detailed review of the accumulated data indicates that for both the social and emotional skills, benefits from the interaction with the rabbit were observed. For both the four and five year old children the positive traits of cooperation, helpfulness, sharing, caring and curiosity occurred more frequently. Conversely the negative trait of aggression, selfishness, anger anxiety, and envy were infrequently observed and was usually observed in the same individual. As Bronfenbrenner stated, interactions are not limited to people and that the object, in this case the rabbit, must be one that will invite attention, exploration, manipulation, elaboration and imagination. With the continued effort of the teacher to incorporate the rabbit in all aspect of the class activities, the children's interest is maintained as they continue to increase their knowledge about the rabbit and their relationship with it evolves into understanding and caring. It can therefore be derived that the presence of the rabbit brought out the positive traits in the children,which far outweigh the negative traits. From these findings, it can clearly be seen that having a rabbit inside the classroom has many benefits. it is therefore recommended that the addition of a school pet be considered when designing a curriculum. The initial investment and the maintenance cost of the rabbit or any pet may seem to be an unnecessary cost for the school, but when the benefits are examined, the cost seems inconsequential. Also the varied pets and wide variety of pet food available will leave the school with many options to choose from leaving the school little reason not to have a pet in the classroom. Parents with children who are shy, withdrawn, with learning disabilities, and only child and special children should consider having a pet at home. Finally, researchers are encouraged to pursue studied on the same topic considering different variables.